Crack path in liquid metal embrittlement: experiments with steels and modeling - T. Auger; S. Hémery; M. Bourcier; C. Berdin; M. Martin; I. Robertson (Fracture and Structural Integrity)
We review the recent experimental clarification of the fracture path in Liquid Metal Embrittlement with austenitic and martensitic steels. Using state of the art characterization tools (Focused Ion Beam and Transmission Electron Microscopy) a clear understanding of crack path is emerging for these systems where a classical fractographic analysis fails to provide useful information. The main finding is that most of the cracking process takes place at grain boundaries, lath or mechanical twin boundaries while cleavage or plastic flow localization is rarely the observed fracture mode. Based on these experimental insights, we sketch an on-going modeling strategy for LME crack initiation and propagation at mesoscopic scale. At the microstructural scale, crystal plasticity constitutive equations are used to model the plastic deformation in metals and alloys. The microstructure used is either extracted from experimental measurements by 3D-EBSD (Electron Back Scattering Diffraction) or simulated starting from a Voronoï approach. The presence of a crackwithin the polycrystalline aggregate is taken into account in order to study the surrounding plastic dissipation and the crack path. One key piece of information that can be extracted is the typical order of magnitude of the stress-strain state at GB in order to constrain crack initiation models. The challenges of building predictive LME cracking models are outlined.